2020
DOI: 10.1093/mnras/staa931
|View full text |Cite
|
Sign up to set email alerts
|

Post-Born corrections to the one-point statistics of (CMB) lensing convergence obtained via large deviation theory

Abstract: Weak lensing of galaxies and CMB photons through the large-scale structure of the Universe is one of the most promising cosmological probes with upcoming experiments dedicated to its measurements such as Euclid/LSST and CMB Stage 4 experiments. With increasingly precise measurements, there is a dire need for accurate theoretical predictions. In this work, we focus on higher order statistics of the weak lensing convergence field, namely its cumulants such as skewness and kurtosis and its onepoint probability di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…An obvious place to start would be with introducing multiple source redshifts to examine the constraining power of a tomographic analysis, which Liu et al (2018) found produced significant improvements in forecasted constraints on Mν . In Barthelemy et al (2020c), the model for the PDF outlined in this work was applied to the CMB lensing PDF, and the cosmological constraints achievable with such a formalism would be another interesting avenue for exploration, although the non-Gaussian information content is smaller so the PDF might be a relatively weaker measurement in this case. This can easily be re-written in terms of φ cyl (y), which is the form that is implemented in our code.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious place to start would be with introducing multiple source redshifts to examine the constraining power of a tomographic analysis, which Liu et al (2018) found produced significant improvements in forecasted constraints on Mν . In Barthelemy et al (2020c), the model for the PDF outlined in this work was applied to the CMB lensing PDF, and the cosmological constraints achievable with such a formalism would be another interesting avenue for exploration, although the non-Gaussian information content is smaller so the PDF might be a relatively weaker measurement in this case. This can easily be re-written in terms of φ cyl (y), which is the form that is implemented in our code.…”
Section: Discussionmentioning
confidence: 99%
“…As we have mentioned in section II, while these terms are often called "post-Born" in the literature (e.g. [51,52]), the Weyl potentials Ψ W in the integrands are evaluated along the unperturbed path x, and hence morally speaking we are still applying the Born Approximation.…”
Section: Equivalence Of the Remapping And Boltzmann Methodsmentioning
confidence: 99%
“…Although they could affect the higher-order (joint) cumulants we are computing and the convergence PDF, it was showed analytically in Bernardeau et al (1997) and numerically in Petri et al (2017) that the effect on the convergence skewness for the sources and scales of interest is negligible. A prescription to include those effects, mostly relevant in the context of CMB lensing, in the depicted formalism i.e large deviation theory was given in Barthelemy et al (2020b).…”
Section: Aperture Mass Definitionmentioning
confidence: 99%
“…The mental image one could form is that of clustered chunks of matter blurred by these lensing terms. Those corrections were shown to be of little importance in the case of the PDF of the convergence field at scales relevant for perturbation theory (θ ∼ 10 arcmin) and relatively small redshifts relevant for upcoming cosmic shear surveys such as Euclid/LSST (z ∼ 1 − 2) (Barthelemy et al 2020b).…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation